1970
DOI: 10.1136/jcp.23.7.594
|View full text |Cite
|
Sign up to set email alerts
|

A fluorimetric and enzymatic method for the estimation of serum total bile acids

Abstract: The enzymatic technique using 3α-hydroxysteroid dehydrogenase for determining bile acids in blood has been modified by measuring the reduced nicotinamide adenine dinucleotide fluorimetrically. The increased sensitivity attained enables the concentration of total bile acids in serum to be estimated using 3 ml for normal subjects and 1 ml for jaundiced patients. The range of normal values in serum was found to be 0-4·7 μmol/litre for males and 1·0-8·2 μmol/litre for females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
1
1

Year Published

1976
1976
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(85 citation statements)
references
References 13 publications
1
82
1
1
Order By: Relevance
“…Serum bile acid levels were not affected by sex (Schwarz et al 1974; Shaffer and Gordon 1978; Barbara et al 1980;Starkey and Marks 1982), whereas the levels are slightly high in females (Murphy et al 1970) or in males (Mashige et al 1976). The results of the present study indicated that no sex-related differences could be observed statistically for any of serum bile acids in all age groups, suggesting that age and sex insignificantly affect bile acid metabolic profiles in healthy adults as far as serum bile acids are concerned and serum bile acid determinations are clinically useful as a liver function test in a wide range of age.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Serum bile acid levels were not affected by sex (Schwarz et al 1974; Shaffer and Gordon 1978; Barbara et al 1980;Starkey and Marks 1982), whereas the levels are slightly high in females (Murphy et al 1970) or in males (Mashige et al 1976). The results of the present study indicated that no sex-related differences could be observed statistically for any of serum bile acids in all age groups, suggesting that age and sex insignificantly affect bile acid metabolic profiles in healthy adults as far as serum bile acids are concerned and serum bile acid determinations are clinically useful as a liver function test in a wide range of age.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier studies have partially included healthy subjects as old as those in our study (Murphy et al 1970;Schwarz et al 1974;Mashige et al 1976 ;Shaffer and Gordon 1978;Starkey and Marks 1982). When the correlation of age to serum bile acid levels in a large proportion of healthy adults was studied by the enzymatic fluorometric method, no age-related differences were observed for PBA, TBA and P/T ratio which reflects the conditions of intestinal microflora and serum bile acid levels in adults were maintained at nearly normal levels even at very advanced age.…”
Section: Discussionmentioning
confidence: 97%
“…Bile salt concentration was determined by the 3␣-hydroxysterol dehydrogenase method. 35 Cholesterol and phospholipids were measured after lipid extraction 36 according to the methods of Gamble et al 37 and Bötcher et al, 38 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Bile salts were measured enzymatically. 21 Commercially available kits were used for the determination of unesterified and total cholesterol, triglycerides (Roche, Mannheim, Germany), phospholipids and free fatty acids (Wako, Neuss, Germany) in plasma. Hepatic and biliary lipids were extracted following Bligh and Dyer.…”
Section: Methodsmentioning
confidence: 99%